Antoni in the kitchen - Porowski, Antoni; Fox, Mindy (Houghton Mifflin Harcourt, 2019)
Antoni Porowski, the food and wine guru on Netflix's sensation Queer Eye, meets people where they live<U+2014>literally. With appealing vulnerability, he shows cooks of all levels how to become more confident and casual in the kitchen. The verve and naturalness of his approach earned raves from Food & Wine and Bon Appétit to GQ and the New York Times, which noted his dishes prove that “sometimes simple is anything but simplistic.” Some of the recipes in this book are weeknight healthyish meals, while others are perfect for off-the-cuff entertaining. Visual stunners, they<U+2019>re often composed of fewer than five ingredients. Whether Bastardized Easy Ramen; Malaysian Chili Shrimp; Roasted Carrots with Carrot-Top Pesto; or Salty Lemon Squares, all can be carried off with panache, even by beginners.